Drawing - Scott, Curie (Emerald Publishing Limited, 2021)
Drawings are everywhere. Daubed on ancient cave walls and projected on screens. Drawings helps us describe science, depict emotions and discover. Yet many of us laid aside drawing - or more simply, mark-making - in childhood, thereby losing a rich and varied way to tell our stories. This book gathers research evidence to demonstrate the substantial value of drawing for health, healthcare and improving wellbeing. It is for anyone interested in engaging in drawing - the low-cost, low-tech, and flexible process which is easily tailored to clients, parents, carers and professionals. The activities featured in the book are distilled from the author's experience of two decades facilitating drawing. Drawing is easily integrated in health and wellbeing contexts and benefits both our mental and physical health. Practically, it can record observations, make visual notes, invite the telling of important stories, improve stress and anxiety, express feelings, and explain complexities. This important book encourages readers to enjoy mark-making once again and learn that thinking through drawing is a powerful life skill that enriches health and wellbeing.
Keywords: Drawing -- Therapeutic use.; Drawing -- Psychological aspects.; Medical -- Mental Health.; Therapy & therapeutics.; elektronické knihy; electronic books